Assessment of heavy metals contamination in estuaries area of Sungai Kilim, Pulau Langkawi - Mohamad Azlan, Mohamad Sajjad; Tajam, Jamil; Mohd Ishak, Mohd Azlan; Ahmad Kamil, Khairunnisa; Mohd Bukhari, Azmil Munif (Faculty of Applied Sciences, 2025)
Heavy metal pollution poses a critical environmental challenge, particularly in estuarine ecosystems such as the Kilim River in Langkawi, Malaysia. This study investigates the distribution of heavy metals (Co, Cr, Fe, Pb, and Zn) in sediment samples collected from 16 locations in Sungai Kilim using the aqua regia closed digestion method. Sediments were processed to prevent contamination, including soaking in 5% nitric acid, drying, pulverizing, and sieving before analysis. Inductively coupled plasma optical emission spectrometry (ICP-OES) was employed for precise analysis, with accuracy validated through reference material testing. The concentrations of heavy metals varied, with Co ranging from 4.50 to 68.49 ppm, Cr from 12.55 to 184.26 ppm, Fe from 0.83% to 4.48%, Pb from 3.42 to 76.55 ppm, and Zn from 11.90 to 75.20 ppm. Enrichment factor calculations showed no significant enrichment for Co (2.354), Cr (2.019), and Zn (1.532), but Pb displayed a moderately severe enrichment (6.198), indicating significant contamination. The findings highlight notable heavy metal concentrations in Sungai Kilim sediments, particularly for lead, suggesting environmental risks exacerbated by industrial and urban activities. These results emphasize the need for targeted environmental management strategies to mitigate contamination and safeguard the ecological health of the estuarine ecosystem.